174 Sclerosing dermopathy after alemtuzumab for multiple sclerosis. Issue 12 (14th November 2019) - Marastoni, Damianou; Lai-Cheong, Joey; Magliozzi, Roberta; Calabrese, Massimiliano; Nicholas, Richard
Abstract : A 48 year-old female with relapsing-remitting multiple sclerosis, diagnosed in 2015, who had failed dimethyl-fumarate treatment with clinical and radiological disease activity - confirmed by a MRI with Gadolinium in January 2018, was started on Alemtuzumab in March 2018. In August 2018, despite clinical improvement, she developed an itchy and painful symmetrical papules in her legs. Skin biopsy showed a patchy perivascular and interstitial inflammatory infiltrate with increased dermal spindle cell numbers most of which had a slender fibrocytic morphology. She partially responded to topical steroids. Clinical and skin histological features indicated nephrogenic systemic fibrosis, a condition usually associated with Gadolinum exposure and renal impairment. There was no evidence of renal disease and bloods excluded other skin fibrotic disorders. The additional histological pattern of interstitial dermatitis seen here, is often observed as a drug reaction. Together these suggested a possible role of Alemtuzumab exposure, though this has not been described. Delayed adverse reactions, in particular B and T cell-driven secondary autoimmunity, are common after Alemtuzumab treatment and indicate the need for long term monitoring of patients exposed to the drug.